Molecular epidemiology of drug-resistant malaria in western Kenya highlands - Menge David M; Cui Liwang; Githeko Andrew; Afrane Yaw; Zhong Daibin; Yan Guiyun (BMC Infectious Diseases, 2008)
Abstract Background Since the late 1980s a series of malaria epidemics has occurred in western Kenya highlands. Among the possible factors that may contribute to the highland malaria epidemics, parasite resistance to antimalarials has not been well investigated. Methods Using parasites from highland and lowland areas of western Kenya, we examined key mutations associated with Plasmodium falciparum resistance to sulfadoxine – pyrimethamine and chloroquine, including dihydrofolate reductase (pfdhfr) and dihydropteroate synthetase (pfdhps), chloroquine resistance transporter gene (pfcrt), and multi-drug resistance gene 1 (pfmdr1). Results We found that >70% of samples harbored 76T pfcrt mutations and over 80% of samples harbored quintuple mutations (51I/59R/108N pfdhfr and 437G/540E pfdhps) in both highland and lowland samples. Further, we did not detect significant difference in the frequencies of these mutations between symptomatic and asymptomatic malaria volunteers, and between highland and lowland samples. Conclusion These findings suggest that drug resistance of malaria parasites in the highlands could be contributed by the mutations and their high frequencies as found in the lowland. The results are discussed in terms of the role of drug resistance as a driving force for malaria outbreaks in the highlands.